The formulation of new model of decision-making process in Malaysian local government - Ngah, Kamarudin; Vyas, Ravindra Nath; Abdul Rahman, Mohd Fitri; Zakaria, Zaherawati (2016)
Currently we are witnessing significant changes in the nature of policy making and management at local government level.These changes represent a move away from the relatively passive approach to a more purposeful approach in which local authorities attempt to learn about the nature of local problems and to respond accordingly. Thus, this paper tries to propose a model of decision-making process for greater performance in local government by taking Malaysian local government as a case.In the findings, there are a few factors influencing councilors in running their functions. It shows that councilors as representatives at local government level will be a good policy maker in handling local issues by adopting this proposed model.In future research, in order to have a greater practice of rational decision-making, perhaps the stakeholders such as households, business communities, community leaders and non-government organizations will be collaborated effectively with councilors in decision making process relates to local affairs.